Morphology of Three Sphyrion (Copepoda: Siphonostomatoida: Sphyriidae) Species Infecting Teleost Fishes off South Africa with the First Description of Males of Two Species. - Dippenaar, S.M. & M.M. Sebone (Diversity-Basel, 2022)
Sphyrion is a member of the family Sphyriidae and currently consists of three valid species, namely S. laevigatum, S. lumpi and S. quadricornis. Species of Sphyrion are mesoparasites of a variety of bony ?shes and occur worldwide. The bodies of the post-metamorphosis females are highly transformed with an elongated cephalothorax bearing conspicuous lateral processes. The structure of the cephalothorax is mostly used in the identi?cation of the different species. The morphology of the adult males resembles those of the lernaeopodid males. Species of Sphyrion were collected from various ?sh hosts off the Indian and Atlantic Oceans off South Africa. Selected specimens were studied using dissection and compound light microscopy as well as scanning electron microscopy. Similar to previous reports, the morphology of specimens of the same species infecting the same host species is highly variable; thus, the structure of the cephalothorax should be considered together with the rest of the body features for identi?cation. Additional information is provided regarding the morphology and armature of the appendages of the post-metamorphosis females of all three species, which resemble previous descriptions, although no detailed comparisons could be done. This is the ?rst collection of descriptions and illustrations of the males of S. laevigatum and S. quadricornis. Male appendages of all three species are very similar with small differences in the armature. New geographical and host reports of the Sphyrion species are provided.